HIV-1 drug resistance in adults and adolescents on protease inhibitor-based antiretroviral therapy in KwaZulu-Natal Province, South Africa - Benjamin Chimukangara; Richard J. Lessells; Benn Sartorius; Lilishia Gounder; Sontaga Manyana; Melendhran Pillay; Lavanya Singh; Jennifer Giandhari; Kerusha Govender; Reshmi Samuel; Nokukhanya Msomi; Kogieleum Naidoo; et al. (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: In low–middle-income countries, increasing levels of HIV drug resistance (HIVDR) on second-line protease inhibitor (PI)-based regimens are a cause for concern given the limited drug options for third-line antiretroviral therapy (ART). We conducted a retrospective analysis of routine HIV-1 genotyping laboratory data from KwaZulu-Natal, South Africa, to describe the frequency and patterns of HIVDR mutations and their consequent impact on standardised third-line regimens. Methods: This was a cross-sectional analysis of all HIV-1 genotypic resistance tests conducted by the National Health Laboratory Service in KwaZulu-Natal (January 2015 to December 2016) for adults and adolescents (age ≥10 years) on second-line PI-based ART with virological failure. We assigned a third-line regimen to each record based on a national treatment algorithm and calculated the genotypic susceptibility score (GSS) for that regimen. Results: Of 348 samples analysed, 287 (82.5%) had at least one drug resistance mutation (DRM) and 114 (32.8%) had at least one major PI DRM. Major PI resistance was associated with longer duration on second-line ART (aOR per 6-months = 1.11, 95% CI 1.04–1.19) and older age (aOR = 1.03, 95% CI 1.01–1.05). Of 112 patients requiring third-line ART, 12 (10.7%) had a GSS of <2 for the algorithm-assigned third-line regimen. Conclusion: One-third of people failing second-line ART had significant PI DRMs. A subgroup of these individuals had extensive HIVDR, where the predicted activity of third-line ART was suboptimal, highlighting the need for continuous evaluation of outcomes on third-line regimens and close monitoring for emergent HIV-1 integrase inhibitor resistance.